Dinamika Pola Komunikasi Orang Tua dan Anak: Sebuah Literatur Review Tersistematis - Anto, Abdul Haris Fitri (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2023)
Communication between parents and children is essential in helping children's development and the psychology of children. Scientific research on this theme has also been conducted with varying results. However, efforts to perform a scoping of these studies remain limited. Therefore, this article aims to examine the literature on the theme of communication patterns between parents and children to generate dynamics comprehensively from the findings of previous studies and serve as inspiration for future studies. This study applied a scoping review method. The search and collection of literature is derived from the Google Scholar page based on the publications of the last ten years (2013-2023). The selected literature was evaluated using Preferred Reporting Items for Systematic Reviews (PRISMA). Based on these steps, 38 literatures were selected for review. The scoping review resulted in four significant discussions: The communication patterns between parents and children on child development, the child's environment, sexuality, and internal family relationships. Furthermore, communication disclosure and democratic/authoritative communication patterns consistently contribute positively to the relationship between parents and children. The implications of the findings and research opportunities are discussed further.